Helicobacter pylori associated newly diagnosed Immune thrombocytopenia in a child with Down syndrome: A case report - Arushi Agarwal; Mridul Malhotra; Amit Badola; Siddharth Sood; Vimal Sekar (Elsevier, 2023)
Background: Immune thrombocytopenia (ITP) is an autoimmune disorder characterized by isolated thrombocytopenia. There can be multiple underlying causes which need to be addressed. Helicobacter pylori (H. pylori) infection is one such cause, but there is paucity of data to support its association with newly diagnosed ITP in children. Case report: We report a case of a child with Down syndrome with Graves' disease who initially presented with pancytopenia, but later developed isolated thrombocytopenia. There were multiple possible etiologies including parvovirus B19 which resulted in delay in treatment in our patient. On detailed work up, she was found to have H. pylori infection. The patient eventually responded to H. pylori eradication therapy. Conclusion: Work up for H. pylori in pediatric age group needs to be considered in case of unexplained thrombocytopenia before labeling it as primary ITP. H. pylori eradication therapy as a part of treatment for H. pylori associated newly diagnosed ITP requires to be studied on larger sample size.